2018
DOI: 10.1038/s41419-018-0981-3
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1-dependent RND1 transcription induced by topoisomerase I cleavage complexes confers cellular resistance to camptothecin

Abstract: RHO GTPases regulate essential functions such as the organization of the actin cytoskeleton. The classic members cycle between an active GTP-bound and an inactive GDP-bound conformation whereas atypical members are predominantly GTP-bound. Besides their well-established role, the classic RHO GTPases RHOB and RAC1, are rapidly induced and/or activated by genotoxic stress and contribute to the DNA damage response. Here we used camptothecin, a selective topoisomerase I (TOP1) inhibitor that stabilizes TOP1 cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…As we reported that the topoisomerase I (Top1) poison camptothecin can transiently enhance nuclear DNA:RNA hybrids at short times in cancer cells (22), we wondered whether FG and PDS can also poison Top1. We then measured Top1-DNA cleavage complexes in U2OS cells, as described (23). The results showed that PDS and FG are not Top1 poisons (SI Appendix, Fig.…”
Section: G4mentioning
confidence: 99%
“…As we reported that the topoisomerase I (Top1) poison camptothecin can transiently enhance nuclear DNA:RNA hybrids at short times in cancer cells (22), we wondered whether FG and PDS can also poison Top1. We then measured Top1-DNA cleavage complexes in U2OS cells, as described (23). The results showed that PDS and FG are not Top1 poisons (SI Appendix, Fig.…”
Section: G4mentioning
confidence: 99%
“…In adenoid cystic carcinoma [52] and in breast cancer [10], the deletion of RND1 gene concerns only one of the two alleles. In several tumors, it has been reported that methylation of RND1 promoter and histone deacetylation induce the repression of RND1 gene transcription [10,46,53,54] (Figure 3). Moreover, in breast cancers, the Polycomb Repressor Complex 2 is involved in the inhibition of RND1 gene expression [10].…”
Section: Rnd1 Expression In Cancersmentioning
confidence: 99%
“…RND1 mRNA is also induced in human lymphocytes 15 min after ionizing irradiation [62]. Using a RT-qPCR screen of Rho GTPase expression in response to the topoisomerase I inhibitor camptothecin, we identified RND1 as a Rho GTPase gene, which is rapidly induced in the osteosarcoma U2OS cell line [53]. The poly (ADP-ribose) polymerase (PARP-1) activity is responsible for the induction of RND1 transcription after treatment with camptothecin (Figure 3).…”
Section: Rnd1 In Response To Anticancer Agentsmentioning
confidence: 99%
See 2 more Smart Citations